Private Equity Firms Capabilities for Buy and Build Strategy - , Akhmad Maulana Hamzah, Nurul Indarti, SE, Sivilokonom, Cand. Merc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study investigates the required capabilities for implementing buy and build strategy in PE firms and the industry preference among the buy and build and non-buy and build implementer firms. We found that networking capabilities and parenting capabilities are essentially vital for implementing buy and build strategy. Experience is suspiciously important capabilities as we check for its robustness using alternative proxy. We also uncover that there is no industry preference between buy and build implementer and non-buy and build implementer firms.